Design, fabrication, and characterization of kinetic-inductive force sensors for scanning probe applications - Roos, August K.; Scarano, Ermes; Arvidsson, Elisabet K.; Holmgren, Erik; Haviland, David B. (Beilstein Journal of Nanotechnology, 2024)
We describe a transducer for low-temperature atomic force microscopy based on electromechanical coupling due to a strain-dependent kinetic inductance of a superconducting nanowire. The force sensor is a bending triangular plate (cantilever) whose deflection is measured via a shift in the resonant frequency of a high-Q superconducting microwave resonator at 4.5 GHz. We present design simulations including mechanical finite-element modeling of surface strain and electromagnetic simulations of meandering nanowires with large kinetic inductance. We discuss a lumped-element model of the force sensor and describe the role of an additional shunt inductance for tuning the coupling to the transmission line used to measure the microwave resonance. A detailed description of our fabrication is presented, including information about the process parameters used for each layer. We also discuss the fabrication of sharp tips on the cantilever using focused electron beam-induced deposition of platinum. Finally, we present measurements that characterize the spread of mechanical resonant frequency, the temperature dependence of the microwave resonance, and the sensor’s operation as an electromechanical transducer of force.
Keywords: atomic force microscopy; force sensing; kinetic inductance; optomechanics; superconductivity